Comparison of alive and dead benthic foraminiferal fauna off the Changjiang Estuary: Understanding water-mass properties and taphonomic processes - Jiang, Feng; Fan, Daidu; Zhao, Quanhong; Wu, Yijing; Ren, Fahui; Liu, Yan; Li, Ang (Frontiers in Marine Science, 2023)
Benthic foraminifera (BF) are used for palaeo-environmental reconstruction based on knowledge of how living individuals respond to environmental variations. However, we still lack enough empirical insights into how non-environmental factors, typically taphonomic processes, affect fossil BF preservations into strata. Here, we compare spatial distribution and compositions of alive and dead BF faunas in surface sediments to illuminate how well fossil BF assemblages mirror quasi-contemporary alive BF groups indicative of different water masses off a mega-river (Changjiang) estuary with intense and complex river-sea interactions. Water mass properties were determined by on-site measurements of bottom water salinity, temperature, and dissolved oxygen in summer. The evaluation was carried out by same-site comparison of alive (Rose Bengal stained) and dead faunas in surface sediment samples over 73 stations. BF assemblages were discriminated using Q-mode Hierarchical clustering analysis based on the relative abundance of common species. Three unique regions with different water-mass properties were identified. The distribution pattern of dead BF faunas is mainly inherited from alive faunas, while density and diversity of the dead faunas are higher than those of the alive faunas. The alive and dead BF faunas are both clustered into 4 assemblages. A few common alive species (small-agglutinated and thin-calcareous) are rarely found in dead faunas, and a few common dead species (preferring low-temperature and allochthonous) are rarely present in alive faunas. The alive BF abundance and diversity are mainly determined by food resources and environmental properties of salinity and temperature. Alive BF assemblages are separated by different water masses determined by river-sea interactions off the Changjiang Estuary. “Time-averaging” effect is responsible for higher density and diversity of the dead BF faunas. Disintegration of agglutinated tests, dissolution of calcareous tests and selective transportation contribute to different species compositions between the alive and dead BF faunas. Nevertheless, indicative species-environment relations in alive and taphocoenose faunas are almost homologous among most common BF species. The results display the effectiveness to integrate the selective BF communities with unique water masses in coastal seas.